2001
DOI: 10.1148/radiol.2203000998
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery for Solitary Parathyroid Adenomas in Patients with Primary Hyperparathyroidism: Role of US with Supplemental CT

Abstract: US examination of patients with primary hyperparathyroidism allowed successful selection for minimally invasive surgery in more than two-thirds of the cases, with additional CT useful chiefly for surgical road mapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 18 publications
2
33
0
6
Order By: Relevance
“…The success of minimally invasive parathyroidectomy depends on the appropriate selection of candidates-namely, those with localizable adenomas on preoperative imaging. 18 A number of imaging modalities, including radionuclide scintigraphy, sonography, and CT, are currently used, both alone and in combination, for localization purposes, with varying levels of success.…”
Section: Discussionmentioning
confidence: 99%
“…The success of minimally invasive parathyroidectomy depends on the appropriate selection of candidates-namely, those with localizable adenomas on preoperative imaging. 18 A number of imaging modalities, including radionuclide scintigraphy, sonography, and CT, are currently used, both alone and in combination, for localization purposes, with varying levels of success.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In some studies, US sensitivity decreased in the presence of multinodular goiter and when the adenoma was located in sonographically ''silent'' regions, such as the upper mediastinum and the retroesophageal area. 3,6,17 To perform a minimally invasive parathyroidectomy, the surgeon must have precise information on the location of the adenoma in the neck. In this study, we evaluated the ability of US to pinpoint the adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Single-phase arterial imaging has been advocated in 1 study as an adjunctive test to sonography. 1 We found that imaging in the arterial phase alone could be helpful, based on the tissue-vascular ratios, but there would be foreseeable circumstances in which high-attenuation thyroid nodules may be difficult to differentiate from PTH-secreting lesions. Kutler et al 10 address this potential pitfall by combining an early postcontrast phase (50 seconds delay) with a noncontrast phase CT. We did not study the role of the noncontrast phase and compare it with our protocol, but an advantage of our protocol, with 2 contrasted phases, is that it provides contrast washout information, which allows potential lesions to be assessed visually or quantitatively in the form of calculated relative enhancement washout percentages.…”
Section: Discussionmentioning
confidence: 87%